2018
DOI: 10.48550/arxiv.1811.00713
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coarse-grained lattice protein folding on a quantum annealer

Tomáš Babej,
Christopher Ing,
Mark Fingerhuth

Abstract: Lattice models have been used extensively over the past thirty years to examine the principles of protein folding and design. These models can be used to determine the conformation of the lowest energy fold out of a large number of possible conformations. However, due to the size of the conformational space, new algorithms are required for folding longer proteins sequences. Preliminary work was performed by Babbush et al. [3] to fold a small peptide on a planar lattice using a quantum annealing device. We ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 18 publications
0
30
0
Order By: Relevance
“…Even though introducing the distances reciprocals and deci-mal numbers in the MR model limit the number of designable sites in a system to three, this model enables us to use more realistic energy terms in the Hamiltonian of a design problem on quantum computers, i.e., mimicking the coulomb energies. Our approach in implementing the distances reciprocals and decimal numbers could also be employed in the protein folding studies with quantum computers that are currently limited to the lattice models [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though introducing the distances reciprocals and deci-mal numbers in the MR model limit the number of designable sites in a system to three, this model enables us to use more realistic energy terms in the Hamiltonian of a design problem on quantum computers, i.e., mimicking the coulomb energies. Our approach in implementing the distances reciprocals and decimal numbers could also be employed in the protein folding studies with quantum computers that are currently limited to the lattice models [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike conventional approaches, quantum computation techniques are expected to enhance solving the NP class of problems in their exact forms [3]. In recent years, there have been attempts on using quantum computers to solve NP-hard problems in protein studies, mainly focused on protein folding [11][12][13][14]. In these studies, hybrid quantum-classical algorithms such as the Quantum Approximate Optimization Algorithm (QAOA) [15] and the Variational Quantum Eigensolver (VQE) [16] are implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Babbush et al showed that such a model can be reduced to PUBO, which paves the way to applying quantum annealers and their simulators in the protein folding problem [37]. Although lattice protein folding is a toy-model, it has been shown to predict model protein tertiary structures to remarkable accuracy [51].In what follows, we briefly discuss the idea behind this reduction.…”
Section: A Lattice Protein Foldingmentioning
confidence: 99%
“…In particular, the protein folding problem -which has been studied classically for decades [1][2][3][4] -has been the subject of a number of quantum studies in recent years [5][6][7][8][9][10]. However, although these works have made important contributions to our understanding of how quantum computers may be applied to this domain, they have either been restricted to lattice-based toy models of proteins or have been based on methods which lack theoretical performance guarantees such as quantum annealing or the quantum approximate optimization algorithm.…”
Section: Introductionmentioning
confidence: 99%